Mechanism of Shenyuan Yiqi Huoxue capsule alleviating coronary microvascular dysfunction: network analysis and experimental evidence - Chen, Jiaping; Zhou, Huiwen; Liu, Hongxu; Li, Xiang; Zong, Huiqi; Zhang, Shuwen; Li, Yunze; Shi, Yuxin (Frontiers in Pharmacology, 2025)
BackgroundShenyuan Yiqi Huoxue Capsule (SYYQ) has clinical evidence to improve coronary microvascular dysfunction (CMD) by tonifying qi and removing blood stasis, but the underlying mechanism remains unclear.ObjectiveThis study aims to explore the mechanism by which SYYQ alleviates CMD through a combination of network analysis and both in vivo and in vitro experiments.MethodsFirst, network pharmacology was employed to predict the mechanism of SYYQ on CMD. Building upon the findings of network pharmacology, we conducted in vivo experiment to verify the improvement mechanism of SYYQ in CMD rats using echocardiography, histopathology, serum biochemistry, TUNEL staining, and transmission electron microscopy (TEM). In the context of cell experiments, we evaluated the characteristic changes in mice cardiac microvascular endothelial cells (MCMECs) and the molecular mechanism of SYYQ through cell transfection, TEM, Western blotting, and qRT-PCR.ResultsThe results of network pharmacology suggest that SYYQ may enhance CMD through pathways related to apoptosis and vascular growth. Animal experiments demonstrated that SYYQ alleviated apoptosis, promoted microvascular opening, and reduced myocardial injury in CMD rats. Furthermore, cell experiments indicated that SYYQ mitigated apoptosis in hypoxic (Hyp) MCMECs, promoted the production of angiogenic factors. Furthermore, downregulation of miR-302-3p levels and activation of Hippo pathway were observed in Hyp MCMECs, which can be inhibited by SYYQ. When miR-302a-3p was overexpressed or the Hippo pathway was inhibited, the efficacy of SYYQ in promoting the production of angiogenic factors and inhibiting apoptosis in Hyp MCMECs was significantly enhanced. Additional studies revealed that miR-302a-3p negatively regulated LATS2.ConclusionSYYQ improves CMD by promoting the production of angiogenic factors and inhibiting apoptosis via miR-302a-3p/Hippo.